THE EFFECT OF RELATIVE CONCENTRATION OF NO AND O2 IN A THREE COMPONENT NO-CO-O2 REACTION FOR THE ELEY-RIDEAL MECHANISM - Qaisrani, A. U.; Khalid, M.; Akhtar, B. Y. (The Nucleus, 2012)
Monte Carlo simulations have been used to explore the effect of the Eley-Rideal (ER) mechanism for three component CO-NO-O2 heterogeneous catalytic reaction on hexagonal lattice. The system is studied for CO and XO; where XO is NO and O2 with ratio NO:O2. The effect of ratio NO:O2 on the catalytic reduction of NO into N and O and oxidation of CO to CO2 are introduced into the model. Many observations are recorded in this three component reaction. It is observed that with the inclusion of ER mechanism with the Langmuir-Hinshelwood (LH) mechanism, a second order phase transition is eliminated and production of CO2 and N2 starts as soon as the CO partial pressure departs from zero. The phase diagrams of the surface coverage with CO, N, O and the steady state production of CO2 and N2 are shown as a function of partial pressure of CO in the gas phase.